Communicating corporate social responsibility: how messages in text influence the standards - Mohd Hasan, Nurul Ain (Universiti Putra Malaysia Press, 2015)
Engaging in corporate social responsibility (CSR) not only requires the practice of strategic communication but also the carefully constructed use of messages in reporting CSR in public documents. This is because appropriate usage of messages in corporate documents potentially enhances readability and awareness of companies’ activities in CSR. Strategic reporting projects substance in practising CSR beyond window dressing, a practice that raises the bar in CSR performances. This study aims to create a snapshot of existing CSR standards of Malaysian multinational corporations through the processes of communication in text particularly in the delivery of the content as written in annual reports. A qualitative textual analysis is employed to detect instances of CSR communicated in annual reports. The data provides a discussion surrounding communication as an important process in achieving readability of messages in the area of CSR grounded within communication literature and theories. The study adds value to research in communication and beyond.